2019
DOI: 10.1037/hea0000749
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in multimorbidity and disability: An integrative review.

Abstract: Objective: Multimorbidity is a robust predictor of disability in aging adults, but the mechanisms by which multimorbidity is disabling are not clear. Most existing research focuses on disease-specific phenomena, such as diminished lung capacity in chronic obstructive pulmonary disease, which can result in functional limitations. This review takes a different approach by highlighting the potential role of a biological process—inflammation—that is common to many chronic medical conditions and thus, from a medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 123 publications
1
33
0
6
Order By: Relevance
“…Equally important to a healthy diet, physical activity has the potential to improve inflammatory status and mobility in chronic stroke patients [ 69 ]. Inflammation is common in several chronic diseases [ 70 ]. It shows an association with malnutrition, functional outcomes [ 71 ], and disability [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equally important to a healthy diet, physical activity has the potential to improve inflammatory status and mobility in chronic stroke patients [ 69 ]. Inflammation is common in several chronic diseases [ 70 ]. It shows an association with malnutrition, functional outcomes [ 71 ], and disability [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, age-related frailty was an important factor in physical disability and mortality [ 8 , 24 , 25 ]. Complex interactions such as muscle strength decline [ 24 ], inflammation [ 26 ], neurological disorder [ 27 ] and chronic diseases [ 28 ] in the elderly lead to disability, and these risk factors were also accelerating the occurrence of death [ 24 ]. On the other hand, multi-morbidity was inextricably linked to death and disability in older adults [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in the Brazilian city of Manaus in 2015 found a higher dengue rate in the previous year in persons with multimorbidity 25 . Although the knowledge is still incipient on the biological mechanism that increases the risk of infections among persons with multimorbidity, the mechanism appears to be associated with increased inflammation and the body's decreased immune response capacity 26,27,28 . Nevertheless, it essential to understand this process in greater detail, considering the identification of differences according to morbidity patterns 29 .…”
Section: Discussionmentioning
confidence: 99%